PEMANFAATAN MEDIA SOSIAL DALAM BERDAKWAH PADA MASA COVID-19 DI ACEH - Zulfikar Zulfikar (STIS Nahdlatul Ulama Aceh, 2020)
This research is to explain that the development of da'wah during the Covid-19 Pandemic has hit Indonesia in general and Aceh in particular has provided changes in the use of da'wah media carried out by preachers in Aceh. Where previously the preachers preferred the media pulpit or mass gathering at a place, but during the Covid-19 pandemic it has changed the perception of preachers in carrying out da'wah activities by preferring social media as a media of preaching. Social media is considered safer and easier to reach by the community in order to hear da'wah, according to the health protocol recommended by the government during Covid-19 in Aceh. Among the several social media used by preachers in carrying out their da'wah activities, Facebook social media is more widely used, and Facebook social media is considered easier to use and easier to reach by layers of society compared to other social media. Social media Facebook can directly do live da'wah activities carried out by preachers and the public can immediately watch da'wah activities anywhere as long as there is an internet or wifi connection which is now available anywhere.